Relationships Among Job Burnout, Generativity Concern, and Subjective Well-Being: A Moderated Mediation Model - Lan, Xingniu; Liang, Yinghao; Wu, Guirong; Ye, Haiying (Frontiers in Psychology, 2021)
This study examines the underlying mechanism that connects job burnout, with generativity concern among a sample of 494 police officers. We adopted the Maslach Burnout Inventory(MBI), the Family Adaptability and Cohesion Scale(FACESII), the Loyola Generativity Scale(LGS), and the Satisfaction with life scale(SWLS). The results showed that job burnout had a significant negative predictive effect on both subjective well-being and generativity concern, and subjective well-being played a mediating role between job burnout and generativity concern. In addition, family intimacy and adaptability had a significant negative moderating effect between subjective well-being and generativity concern. In a conclusion, there is a moderated mediating effect between job burnout and generativity concern.